Matched pair analysis to evaluate the impact of hospitalization during radiation therapy as an early marker of survival in head and neck cancer patients. (October 2020) - Han, Hye Ri; Hermann, Gregory M.; Ma, Sung Jun; Iovoli, Austin J.; Wooten, Kimberly E.; Arshad, Hassan; Gupta, Vishal; McSpadden, Ryan P.; Kuriakose, Moni A.; Markiewicz, Michael R.; Chan, Jon M.; Platek, Mary E.; et al.
Highlights: About 20% of RT-treated patients had at least one unplanned hospitalization. Most frequent reasons for admission included dehydration 40% and fever 29%. Artificial nutrition support and post-RT weight loss increased risk of admission. Hospitalized patients had worse OS and CSS than matched non-hospitalized patients. Abstract: Background: Complications from radiotherapy (RT) alone or combined with surgery and/or chemotherapy for head and neck cancer (HNC) sometimes necessitate hospitalization. Our aim was to evaluate the frequency, cause, and survival outcomes associated with hospitalizations in patients undergoing RT for HNC. Patients and methods: Using a retrospective single-institution database, we reviewed hospitalization records of HNC patients treated at Roswell Park Comprehensive Cancer Center with definitive or post-operative RT between 2003 and 2017. Patients who were admitted during treatment and within 90-days post-RT were identified. Multivariate analyses, Kaplan-Meier statistics, and analysis on propensity score matching were performed to obtain matched-pair, after matching baseline characteristics, such as age, gender, smoking, tumor staging, p16 status, and treatments received. Results: 839 patients were eligible for analysis. Median follow-up was 34.8 months (Interquartile range [IQR] 15.6–64.8). 595 (71%) received definitive RT and 244 (29%) received adjuvant RT. Chemotherapy was used in 671 patients (80%). 171 patients (20%) had at least one hospitalization. Dehydration (40%) and fever (29%) were the most frequent causes of admission. Hospitalized patients had significantly worse overall survival (OS) (Hazards ratio [HR] 1.61, 95% CI 1.26–2.07, p < 0.001) and cancer-specific survival (CSS) (HR 1.45, 95% CI 1.07–1.95, p = 0.02). 163 matched pairs had median follow-up of 58.6 months (IQR 37.6–85.0). Median OS was 34.5 months (IQR 13.3–58.0) for hospitalized versus 44.2 months (IQR 20.3–78.7) for non-hospitalized patients (p = 0.01). Conclusion: This study reveals significantly worse OS and CSS for patients hospitalized during RT for HNC. Hospitalization may be an early marker for worse survival.